2014
DOI: 10.1186/1471-2474-15-334
|View full text |Cite
|
Sign up to set email alerts
|

Association between the awareness of osteoporosis and the quality of care for bone health among Korean women with osteoporosis

Abstract: BackgroundThe prevalence of osteoporosis is increasing and is a socio-economic burden worldwide. Although screening tests for osteoporosis in Korea are easily accessible, this condition remains undertreated. Evaluating post-diagnostic behavior changes may be helpful for improving the quality of care for bone health in osteoporotic patients.MethodsAfter reviewing the Fourth Korean National Health and Nutrition Examination Survey 2008–2009, 1,114 women with osteoporosis aged >50 years were included in this cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
0
13
1
Order By: Relevance
“…With respect to behavioral factors in addition to PA, there is strong evidence that excessive alcohol consumption and smoking has a negative influence on bone metabolism (13)(14) . Regarding smoking, we found that smokers and former smokers in our study had lower BMD means than non-smokers, although these differences were not significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to behavioral factors in addition to PA, there is strong evidence that excessive alcohol consumption and smoking has a negative influence on bone metabolism (13)(14) . Regarding smoking, we found that smokers and former smokers in our study had lower BMD means than non-smokers, although these differences were not significant.…”
Section: Discussionmentioning
confidence: 99%
“…In view of this epidemiological situation, the identification of factors associated with bone health is fundamental to combat the progression of osteometabolic diseases. In this sense, studies have shown that age and gender (5)(6)(8)(9)(10) , use of medications and hormones (11)(12) , body composition (6)(7)(8)(9)(10) , behavioral and environmental aspects (13)(14) , and food consumption (15) are factors associated with bone metabolism. However, few studies have been conducted with adults of both genders (4,16) , and the existing studies assess risk factors in isolation (5,15) .…”
Section: Introductionmentioning
confidence: 99%
“…The Peri-M (aged 45-55 years) women's awareness was higher (59%) than the Post-M (age 65+, 19.0%) women, so the screening behaviors were inconsistent with the studies conducted in Korea regarding awareness of osteoporosis of women aged 50 years or older in that they did not differ with age or bone condition (Kim et al, 2012;Shin, Kang, Lee, & Park, 2014). This can be explained as the transitional menopausal status in the Peri-M group might have taken it upon themselves to seek screening.…”
Section: Discussionmentioning
confidence: 63%
“…[23,24] Likewise, our pop-up messages were informative and effective for increasing the awareness of orthopaedic surgeons regarding osteoporosis. Shin et al have emphasized that post-diagnostic care should start with discontinuation of alcohol and initiation of physical exercise, [1] and osteoporosis medications and exercise programmes might be crucial for reducing morbidity and mortality after osteoporotic hip and spine fractures. Bogoch et al [25] described four categories of barriers to osteoporosis treatment: patients, physicians, orthopaedic surgeons and medical care systems.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporotic hip and spine fractures are the clinical manifestation of osteoporosis and have become a socio-economic burden throughout the world. [1,2] These fractures are associated with a high mortality rate and low quality of life, [2,3] although several studies have demonstrated that appropriate osteoporosis treatment after hip or fragility fractures reduces the risks of subsequent fracture and mortality. [4][5][6] However, secondary fracture can occur after osteoporotic hip or spine fractures, which create increases of 5% in the risk of subsequent hip fracture within 1 year, 17-21% in the risk of any fracture within 16-21 months and 29% in the risk of subsequent hip fracture within 20 years.…”
Section: Introductionmentioning
confidence: 99%